The biomechanics of human locomotion - Vaughan, Christopher Leonard (Kit) (Department of Medicine, 2014)
Includes bibliographical references. The thesis on CD-ROM includes Animate, GaitBib, GaitBook and GaitLab, four quick time movies which focus on the functional understanding of human gait. The CD-ROM is available at the Health Sciences Library.